Radiographic grid for locating foreign bodies in maxillofacial emergency trauma - Ziqi Zhang; Mingliang Yang; Ran Zhang (BMC, 2024)
Abstract Objectives The accurate localization of the foreign bodies (FBs) is essential. This work presents a new noninvasive technique for subcutaneous metallic FBs under a radiographic grid, a system that simplifies the localization of facial FBs removal using a grid with embedded reference points. Methods This work designed a retrospective study to evaluate the effect of a radiographic grid on FBs removal surgery. All patients who met the inclusion criteria and attended the Hospital of Stomatology of China Medical University from January 2022 to June 2023 were enrolled and randomly divided into grid and non-grid groups. The assessment of facial swelling, the primary indicator, was conducted on days 2 and 7 post-surgery. The variables were analyzed using the Student t test and a repeated-measures general linear model. Results The study sample consisted of 20 patients, with 14 males (70%) and 6 females (30%), who had an average age of 30.30 ± 5.38. The average time of operation was 1.85 ± 0.66 h (range 0.7 to 3.2). In the present cases in this report, of the 20 patients' FBs, 14 were metal, 5 were glass, and 1 was residual root. And the FBs were surgically removed with no postoperative complications. Through comparison, it was found that the degree of swelling on day 2 postoperatively was significantly different between the grid group and the non-grid group (P < 0.05). Conclusions This study demonstrates that a radiographic grid with mark points is a more efficient approach compared with traditional methods for FBs removal, and this surgical method is more accurate, fast and noninvasive.